Emotional intelligence - Goleman, Daniel (Bantam Books, 1995)
Is IQ destiny? Not nearly as much as we think. Daniel Goleman's fascinating and persuasive book argues that our view of human intelligence is far too narrow, ignoring a crucial range of abilities that matter immensely in terms of how we do in life.